The future of multilocational work and New Working Spaces in small and medium-sized urban municipalities and in rural municipalities : A Norwegian perspective - Di Marino, Mina; Chavoshi, Seyed Hossein; Andersen, Torhild; Nenonen, Suvi (Routledge, 2024)
Since the early 2000s, several developments in technology, as well as in cultural and economic contexts, have dramatically influenced ways of working in the Nordic countries and beyond. However, there is a lack of a clear overview of the increase in New Working Spaces (NWS) (e.g., coworking areas, public libraries and coffee shops equipped as workspaces, and other collaborative hubs). The aim of the article is to explore the possibilities for multilocational work, including the growth of NWS that are gradually appearing in small and medium-sized urban municipalities and in rural municipalities. The authors conducted a literature review, and they studied the phenomenon empirically by providing a comprehensive overview of the NWS spanning all of Norway, with a main focus on the five counties of Vestland, Agder, Innlandet, Nordland, and Viken. In addition to spatial analyses (including concentration, centrality, and types of spaces), semi-structured interviews were conducted during the COVID-19 pandemic with the managers of NWS. The sample represented hubs emerging recently opened. The findings revealed that varied opportunities exist for multilocational work, including new forms and places for working, which can contribute to revitalizing several districts. An ongoing need is for policymakers, planners, municipalities, and private investors to address future visions and strategies. Peer reviewed